Drupal workshop presentation - Afroz, Hasina; Saleque, Auninda Rumy (BRAC University, 2012)
Presentation on "The Launching Ceremony and Workshop on Using Open Source Content Management System Drupal to build Library Websites" at BRAC University Library.